THE IMPACT OF TAX AGGRESSIVENESS, FIRM SIZE, AND FOREIGN OWNERSHIP TO SOCIAL RESPONSIBILITY - WINNY GRANDIS; ROSINTA RIA PANGGABEAN (Universitas Pamulang, 2018)
Mining companies in Indonesia are companies that explore natural resources as a source of income for the company. The use of mining companies for this study is because the activities undertaken by these companies related to waste and environmental pollution so that the level of industrial risk and environmental damage becomes high. The purpose of this study is to analyze the impact of the tax aggressiveness (ETR), firm size (SIZE), and foreign ownership (FOCI) to corporate social responsibility (CSR) of the mining companies. The population in this study are the mining companies which were listed in Indonesia Stock Exchange from year 2010 to 2015. This study uses tax aggressiveness, firm size, and foreign ownership as independent variables; profitability, leverage, and market-to-book ratio as control variables; and also corporate social responsibility as dependent variable. There are 9 samples of mining companies which produced 54 data using purposive sampling technique. This study use logistic regression method. This study uses Eviews 9 and Microsoft Excel 2007 for data processing. The results showed that the firm size (SIZE) has a significant effect on the company's CSR, while tax aggressiveness and foreign ownership have no significant effect on company’s CSR. This results indicate that the bigger the size of a company will cause greater activities and influences in the society, which make companies pay more attention to social programs and social responsibility disclosures.